Nighttime Blood Pressure Phenotype and Cardiovascular Prognosis: Practitioner-Based Nationwide JAMP Study. Issue 19 (10th November 2020) - Kario, Kazuomi; Hoshide, Satoshi; Mizuno, Hiroyuki; Kabutoya, Tomoyuki; Nishizawa, Masafumi; Yoshida, Tetsuro; Abe, Hideyasu; Katsuya, Tomohiro; Fujita, Yumiko; Okazaki, Osamu; Yano, Yuichiro; Tomitani, Naoko; et al.
Abstract : Background: Ambulatory and home blood pressure (BP) monitoring parameters are better predictors of cardiovascular events than are office BP monitoring parameters, but there is a lack of robust data and little information on heart failure (HF) risk. The JAMP study (Japan Ambulatory Blood Pressure Monitoring Prospective) used the same ambulatory BP monitoring device, measurement schedule, and diary-based approach to data processing across all study centers and determined the association between both nocturnal hypertension and nighttime BP dipping patterns and the occurrence of cardiovascular events, including HF, in patients with hypertension. Methods: This practitioner-based, nationwide, multicenter, prospective, observational study included patients with at least 1 cardiovascular risk factor, mostly hypertension, and free of symptomatic cardiovascular disease at baseline. All patients underwent 24-hour ambulatory BP monitoring at baseline. Patients were followed annually to determine the occurrence of primary end point cardiovascular events (atherosclerotic cardiovascular disease and HF). Results: A total of 6, 359 patients (68.6±11.7 years of age, 48% men) were included in the final analysis. During a mean±SD follow-up of 4.5±2.4 years, there were 306 cardiovascular events (119 stroke, 99 coronary artery disease, 88 HF). Nighttime systolic BP was significantly associated with the risk of atherosclerotic cardiovascular disease and HF (hazard ratio adjusted for demographic and clinical risk factors per 20-mm Hg increase: 1.18 [95% CI, 1.02–1.37], P =0.029; and 1.25 [95% CI, 1.00–1.55], P =0.048, respectively). Disrupted circadian BP rhythm (riser pattern, nighttime BP higher than daytime BP) was significantly associated with higher overall cardiovascular disease risk (1.48 [95% CI, 1.05–2.08]; P =0.024), and especially HF (2.45 [95% CI, 1.34–4.48]; P =0.004) compared with normal circadian rhythm. Conclusions: Nighttime BP levels and a riser pattern were independently associated with the total cardiovascular event rate, in particular for HF. These findings suggest the importance of antihypertensive strategies targeting nighttime systolic BP. Registration: URL: https://www.umin.ac.jp/ctr/ ; Unique identifier: UMIN000020377. Abstract : Supplemental Digital Content is available in the text.